A Phenomenological Inquiry of Student Leaders' Experiences to Develop the Student Development Evaluation Tool of Bacolod City College - Adnan Balisi; Menchie Cuenca; Angelica Apawan; Reyan Ballaso (Research Synergy Foundation, 2025)
This phenomenological inquiry described the universal essence of the student development experience at Bacolod City College (BCC), a Local University and College (LUC), to develop a context-specific, valid Student Development Evaluation Tool. The study addressed a critical gap: existing generic evaluation frameworks are inadequate for the unique, resource-constrained environment of Philippine community colleges. Adopting a phenomenology design, the research captured the subjective realities of twelve (12) purposively selected student leaders from BCC. Data were collected through in-depth, semi-structured interviews and rigorously analyzed using Colaizzi’s Method. The inquiry yielded seven interconnected thematic horizons defining the core phenomenon: the student development experience is characterized by a constant tension between student aspirations and profound institutional limitations. The themes identified were: 1) Operational Exhaustion on Leadership (due to lack of formal training); 2) Organizational Invisibility for Student Engagement (caused by physical and communicative barriers); 3) Mandatory Obligation on Activities (engagement driven by attendance requirements); 4) Unmet Expectations and Support for Arts and Sports (deficient facilities/funding); 5) Personal Subsidy for Resources (leaders absorbing operational costs); 6) Horizon of Bureaucratic Delay (inefficient administrative processes); and 7) Environmental Constraints (inadequate physical facilities). The findings confirm a profound disparity where student efficacy is consistently hampered by systemic infrastructural and organizational deficiencies. This reality fosters a cycle of leader liability and operational exhaustion, relegating student development to a mandatory obligation. The resulting seven-section Student Development Evaluation Tool is directly rooted in these empirical narratives, providing BCC with a context-specific framework to quantifiably measure and address these structural deficiencies, offering a model for evidence-based decision-making for other LUCs.